Mental toughness training circle (MTTC): what is its impact on the mental toughness, anxiety, and academic performance of college-level athletes and non-athletes? - Miftah Fariz Prima Putra; Sutoro Sutoro; Agus Zainuri; Gerdha Kristina Ivony Numberi; Dewi Nurhidayah; Akhmad Kadir (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction and objectives: Even though MTTC is claimed to be a more systematic and comprehensive mental training model, there is not much evidence regarding the impact of implementing the MTTC model on athletes and non-athletes. Based on this, this research aims to examine the impact of the MTTC model mental training on athletes and non-athletes, both on psychological and cognitive aspects.